Pain paths among post‐COVID‐19 condition subjects: A prospective cross‐sectional study with in‐person evaluation - Kubota, Gabriel T.; Soares, Felipe H. C.; Fonseca, Alessandra S.; Rosa, Talita dos Santos; Silva, Valquiria A.; Gouveia, Gisele R.; Faria, Viviane G.; Cunha, Pedro H. M.; Brunoni, André R.; Teixeira, Manoel J.; Andrade, Daniel C. (European journal of pain, 2023)
Background New‐onset chronic pain has been acknowledged as part of the post‐COVID‐19 condition. However, available fine‐grained data about its clinical phenotype, trajectories and main associated characteristics remain scarce. We described the distinct temporal evolutions of post‐COVID‐19 pain and their epidemiological and phenotypical features. Methods A prospective cross‐sectional study enrolled post‐COVID‐19 condition patients (i.e. who had persisting COVID‐19‐related symptoms over 30 days since their first positive laboratory test), whose COVID‐19 diagnosis had been supported by RT‐PCR of oral/nasopharyngeal swab or serology. They underwent in‐person evaluations with a structured interview, pain and quality‐of‐life‐related questionnaires and thorough physical examination. Chronic pain (CP) and probable neuropathic pain (NP) were defined according to IASP criteria. Results The present study included 226 individuals, 177 (78.3%) of whom presented over 3 months since their first COVID‐19 symptom. New‐onset pain occurred in 170 (75.2%) participants and was chronic in 116 (68.2%). A chronic course was associated with COVID‐19‐related hospitalization, new‐onset fatigue, lower cognitive performance, motor and thermal sensory deficits, mood and sleep impairments and overall lower quality‐of‐life levels. Probable NP occurred in only 7.6% new‐onset pain patients, and was associated with pain chronification, new‐onset fatigue, motor and thermal sensory deficits, mechanical allodynia and lower rates of SARS‐CoV‐2 vaccination. Previous CP was reported by 86 (38.1%) individuals and had aggravated after the infection in 66 (76.7%) of them, which was associated with orthostatic hypotension. Conclusions Post‐COVID pain phenomena follow different paths, which are associated with specific clinical and epidemiological features, and possibly distinct underlying mechanisms, prognostic and therapeutic implications. Significance COVID‐19‐related pain usually follows a chronic course and is non‐neuropathic. Its possible courses and phenotypes are associated with distinct clinical and epidemiological features. This suggests differing underlying mechanisms, which may have significant prognostic and therapeutic implications.